(untitled) (Baghdad Science Journal, 2014)
The 2011 Iraqi Measles Control Campaign had as its aim to improve immunization coverage among young adults’ 17-24years and, in the longer term, prevention of measles epidemics. The aim of the study is estimation measles vaccination and revaccination efficacy by evaluate the seroprevalence of antibody and response to reimmunization in young adults. A previously vaccinated 189 young adult medical students were tested for measles specific IgG &IgM pre and post catch-up revaccination by using commercially available ELISA. To assess the seroprevalence of antibody response pre measles reimmunization in previously vaccinated young adults; 45 were found to be seronegative. To differentiate between primary and secondary vaccine failure, anti- measles IgM and IgG titers were assessed again 2-4 weeks after revaccination in 189 seronegative participants [45 seronegative, 144 seropositive individuals: 29 seronegative participants responded to revaccination anamnestically(P < 0.001)and developed immunity; 7 also showed IgM response (probably primary vaccine failure); 144 seropositive participants remained seroprotected without significant increase in antibody titer (P=0.577). Primary vaccine failure was fond to be 3.7%; while secondary vaccine failure was 11.6%.After revaccination, 85.1% were seroprotected. This study demonstrates the waning measles immunity in young adults in Iraqi medical students, which poses the potential risk of transmission of measles. Periodic Serological surveillance and revaccination of susceptible young adults are recommended.